Clinical activity of androgen deprivation therapy in patients with metastatic/relapsed androgen receptor–positive salivary gland cancers. Issue 5 (25th June 2015) - Locati, Laura D.; Perrone, Federica; Cortelazzi, Barbara; Lo Vullo, Salvatore; Bossi, Paolo; Dagrada, Gianpaolo; Quattrone, Pasquale; Bergamini, Cristiana; Potepan, Paolo; Civelli, Enrico; Fallai, Carlo; Pilotti, Silvana; et al.
Abstract: Background: Androgen deprivation therapy has some clinical activity in selected salivary gland cancer histotypes, with androgen receptor expression. Methods: We retrospectively analyzed patients with androgen receptor‐expressing recurrent/metastatic salivary gland cancer, treated with androgen deprivation therapy. Protein expression of androgen receptor and ErbB family members was investigated. Progression‐free survival (PFS) and overall survival (OS) were the main endpoints. Results: Seventeen patients were identified. No significant toxicities were reported. Overall response rate was 64.7%; 3‐year PFS and 5‐year OS were 11.8% and 19.3%, respectively. Androgen receptor overexpression may be sustained by gain of chromosome X (58%) and TP53 mutation (44%). No association between response to androgen deprivation therapy and epidermal growth factor receptor (EGFR), human epidermal growth factor receptor (HER)2, HER3 expression, PIK3CA mutations, or phosphatase and tensin homolog ( PTEN ) deletion was identified. Conclusion: We confirm the activity of androgen deprivation therapy in androgen receptor‐expressing recurrent/metastatic salivary gland cancers. The hypothesis that an androgen receptor increased gene copy number may represent a possible mechanism of primary resistance should be further investigated. © 2015 Wiley Periodicals, Inc. Head Neck 38: 724–731, 2016